Association of persisting IgA response with yersinia triggered reactive arthritis: a study on 104 patients. Issue 12 (December 1987) - Toivanen, A; Lahesmaa-Rantala, R; Vuento, R; Granfors, K
Abstract : Twelve to 16 months after Yersinia enterocolitica O:3 enteritis 33 (85%) of the 39 patients who developed reactive arthritis as a postinfection complication had IgA class and 28 (72%) had IgG class anti-yersinia antibodies. In contrast, 7 (32%) of the 22 patients who did not develop arthritis were positive in the IgA test and 11 (50%) positive in the IgG test. The results were about the same when the material was divided into cases with diagnosis of yersiniosis verified by stool culture or by serology. These results confirm the value of enzyme linked immunosorbent assay (ELISA) in the diagnosis of yersiniosis, particularly in cases with postinfection complications when the stool isolations remain negative.